Venomics of the Australian eastern brown snake (Pseudonaja textilis): Detection of new venom proteins and splicing variants. (1st December 2015) - Viala, Vincent Louis; Hildebrand, Diana; Trusch, Maria; Fucase, Tamara Mieco; Sciani, Juliana Mozer; Pimenta, Daniel Carvalho; Arni, Raghuvir K.; Schlüter, Hartmut; Betzel, Christian; Mirtschin, Peter; Dunstan, Nathan; Spencer, Patrick Jack
Abstract: The eastern brown snake is the predominant cause of snakebites in mainland Australia. Its venom induces defibrination coagulopathy, renal failure and microangiopathic hemolytic anemia. Cardiovascular collapse has been described as an early cause of death in patients, but, so far, the mechanisms involved have not been fully identified. In the present work, we analysed the venome of Pseudonaja textilis by combining high throughput proteomics and transcriptomics, aiming to further characterize the components of this venom. The combination of these techniques in the analysis and identification of toxins, venom proteins and putative toxins allowed the sequence description and the identification of the following: prothrombinase coagulation factors, neurotoxic textilotoxin phospholipase A2 (PLA2 ) subunits and "acidic PLA2 ", three-finger toxins (3FTx) and the Kunitz-type protease inhibitor textilinin, venom metalloproteinase, C-type lectins, cysteine rich secretory proteins, calreticulin, dipeptidase 2, as well as evidences of Heloderma lizard peptides. Deep data-mining analysis revealed the secretion of a new transcript variant of venom coagulation factor 5a and the existence of a splicing variant of PLA2 modifying the UTR and signal peptide from a same mature protein. The transcriptome revealed the diversity of transcripts and mutations, and also indicates that splicing variants can be an important source of toxin variation. Highlights: Pseudonaja textilis venome was analysed by combining transcriptome and proteome. A novel coagulation factor 5a splicing variant was detected by both approaches. A new long three finger toxin was detected by both approaches. Two identical PLA2 s with different UTRs and signal peptides were sequenced.